2016
DOI: 10.1080/09540253.2016.1188197
|View full text |Cite
|
Sign up to set email alerts
|

Perceived differences and preferred norms: Dutch physical educators constructing gendered ethnicity

Abstract: Many physical education (PE) teachers have been challenged by the shift from teaching in primarily ethnic homogenous contexts to multi-ethnic (ME) classes. Teachers in secondary schools often experience difficulty in class management in such classes. This difficulty may limit their ability to create a positive studentteacher relationship and may result in practices of inclusion, exclusion and marginalisation. The purpose of this paper was to explore how Dutch PE teachers construct their relationship with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…Elsewhere we have shown how constructions of students by physical education teachers can endorse certain practices of masculinity, ability and whiteness (Van Doodewaard & Knoppers, 2018). In the current study, PE teachers constructed several bodies as needing care or protection and these bodies were framed as 'being too vulnerable to perform'.…”
Section: Degree Of Perceived Resiliencementioning
confidence: 93%
See 3 more Smart Citations
“…Elsewhere we have shown how constructions of students by physical education teachers can endorse certain practices of masculinity, ability and whiteness (Van Doodewaard & Knoppers, 2018). In the current study, PE teachers constructed several bodies as needing care or protection and these bodies were framed as 'being too vulnerable to perform'.…”
Section: Degree Of Perceived Resiliencementioning
confidence: 93%
“…Feminist researchers have pointed out how the influence of gendered discourses and power relations in PE privilege particular masculinities and simultaneously marginalize femininities, alternative masculinities and sexualities (Gerdin, 2017;Scraton, 1992;Sykes, 2011;Van Doodewaard & Knoppers, 2018;Wrench & Garrett, 2017). For example, Fisette (2011) showed how PE reinforced gendered power relations by sending the message to some of the girls that they are 'not as good as others ' (p. 191).…”
Section: Desirable Bodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have also illuminated how children from minority backgrounds or with disabilities are often placed within homogenous and fixed categories and treated within deficit discourse [15][16][17][18][19]. Within this discourse, children of minority backgrounds or with disabilities are seen as lacking the skills, values, and norms to be recognized as good and competent students in physical education [20]. Scholars have suggested that research has contributed to (re)producing categorical thinking and othering by focusing on how children's characteristics, such as cultural background or ability, act as barriers to participation rather than examining how the subject in Western countries is racialized, white-centric, and embedded in thoughts of Eurocentrism and ableism [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%